2009
DOI: 10.1016/j.ejcts.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous stem cells in patients undergoing coronary artery bypass graft surgery

Abstract: Considerable research efforts have recently been made towards the application of autologous stem cell therapy for cardiovascular regeneration. Patients with coronary artery disease undergoing surgery represent a potential target. As yet, this approach has failed to obtain satisfactory evidence in clinical studies. However, several observational studies have described mobilising effect of cardiac surgery on endogenous stem cells, although the mechanisms of this phenomenon and its clinical relevance are not defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…SC therapy of lymphoproliferative diseases is an established method of challenging a permanent interaction between the graft and the host [46]. Theoretically, in case of more complex organs, an implanted micro-size tissue can be followed by a controlled growth to full size under the supervision of the surrounding tissue microenvironment and additionally administered growth and differentiation factors.…”
Section: Cells Scaffolds and Signalling In The Practice Of Tissue Enmentioning
confidence: 99%
“…SC therapy of lymphoproliferative diseases is an established method of challenging a permanent interaction between the graft and the host [46]. Theoretically, in case of more complex organs, an implanted micro-size tissue can be followed by a controlled growth to full size under the supervision of the surrounding tissue microenvironment and additionally administered growth and differentiation factors.…”
Section: Cells Scaffolds and Signalling In The Practice Of Tissue Enmentioning
confidence: 99%
“…Recent reports have shown involvement of Notch and sphingosine-1 phosphate system signaling in the activation of CXCR4 under conditions of tissue ischemia [68]. Clinical studies have demonstrated, that cardiovascular surgical intervention had mobilizing effect on CD34+, CD34+CXCR4+ cells and increased number of circulating CFU progenitor cells [69].…”
Section: Stem/progenitor Cell Trafficking and Homingmentioning
confidence: 99%
“…It was shown that chronic inflammation interferes with the process of endothelial regeneration and, thereby, contributes to endothelial dysfunction [26]. Attempts were made to use bone marrow derived stem cells for therapeutic purposes in several cardiovascular disorders [27]. Whether this approach will be also useful in chronic inflammatory disorders is not clear.…”
mentioning
confidence: 99%